Language Disorders in Students with Mild Mental Retardation in SLB/Sekolah Luar Biasa (School for Disabled Children) - Ilfan Askul Pehala; Fika Nurul Fadilah; Wawan Gunawan; Ulwia Hamsi (Jurnal Langua, 2023)
ABSTRACT The purpose of this case study is to discuss the differences in language disorders between two female mild mental retardation students. Observation data and semi-structured interviews were analyzed thematically to see differences in language disorders between two female students who have the same mild mental retardation. This research conducted with three participants, one teacher and two is female students who have mild mental retardation. The finding of this study showed that there are some differences between two mild mental retardation students’ language disorders and there are several themes that showed, namely: (1) the Kind of language disorders in two female mild mental retardation students; (2) The using of language in two female mild mental retardation students; (3) Socialization and the development of language in two female mild mental retardation students; (4) The cause of language disorders in two female mild mental retardation students. The result of this study indicates that we should have to give extra energy to analyzing students with mental retardation because they are not similar. They have some differences, in skill and also in their problems (language disorders). It means that even though participants have the same mental retardation, it is not guaranteed that they have the same language disorders. This study suggests to the next researchers could gain data from some students who have several levels of mental retardation. Keywords: Language disorders; Mild mental retardation; Language Acquisitions